Purification and production of monospecific antibody to the hemagglutinin from Subtype H5N1 influenza virus - Tarigan, Simson; Indriani, R; Hewajuli, D (Indonesian Journal of Animal and Veterinary Sciences, 2010)
The purpose of this study was to purify the hemagglutinin from H5N1 virus and to generate monospecific antibody appropriate for production of sensitive and specific immunoassay for H5N1 avian influenza. For this purpose, a local isolate H5N1 virus (A/Ck/West Java/Hamd/2006) was propagated in chicken embryos. The viral pellet was dissolved in a Triton-X-100 solution, undissolved viral particles were pelleted by ultracentrifuge, and the supernatant containing viral surface glycoproteins (Hemagglutinin and neuraminidase) was collected. The neuraminidase in the supernatant was absorbed by passing the supernatant through an Oxamic-acid-superose column. After dialyzing extensively, the filtrate was further fractionated with an anion exchange chromatography (Q-sepharose) column. Proteins adsorbed by the column were eluted stepwisely with 0.10, 0.25, 0.25 and 0.75 M NaCl in 20 mM Tris, ph 8. Hemagglutinin (H5) was found to be eluted from the column with the 0.5 M NaCl elution buffer. The purified H5 was free from other viral proteins based on immunoassays using commercial antibodies to H5N1 nucleoprotein and neuraminidase. When used as ELISAâs coating antigen, the purified H5 proved to be sensitive and specific for hemagglutinin H5. Cross reactions with other type-A-influenza virus, H6, H7 dan H9, were negligibly low. For the production of monospecific antiserum, the purified H5 was separated with SDS-PAGE, the band containing the H5 monomer was cut out , homogenised and injected into rabbits. The antiserum was capable of detecting the presence of inactivated H5N1 virus in a very dilute suspension, with a detection limit of 0.04 heagglutination (HA) unit. The purified hemagglutinin and the serum raised against it should be useful for developing specific, sensitive and affordable immunoassay for H5N1 avian influenza. Key Words: H5N1, Hemagglutinin, Triton, Oxamic-acid Sepharose, Q sepharose, ELISA